2013
DOI: 10.5122/cbirds.2013.0025
|View full text |Cite
|
Sign up to set email alerts
|

A global overview of cranes: status, threats and conservation priorities

Abstract: This paper reviews the population trends and threats for the 15 species of cranes, and comments on conservation priorities for the family as a whole. Cranes occur on five continents, with greatest diversity in East Asia (nine species) and Sub-Saharan Africa (six species). Eleven crane species are threatened with extinction according to the IUCN Red List, including one species Critically Endangered, three species Endangered, and seven species Vulnerable. Of the four species of Least Concern, population sizes fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
91
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(94 citation statements)
references
References 26 publications
0
91
0
3
Order By: Relevance
“…The cranes migrate short distances to winter in the lower altitude (primarily 2,000–3,200 m) Yunnan–Guizhou Plateau (Harris & Mirande, 2013). Through telemetry and banding data, it has become clear that the birds using the Eastern migratory route (in the following referred to as the Eastern Black-necked Cranes) breed in northern Sichuan and southern Gansu provinces and mainly winter in northeast Yunnan and southwest Guizhou (Li & Li, 2005; Qian et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The cranes migrate short distances to winter in the lower altitude (primarily 2,000–3,200 m) Yunnan–Guizhou Plateau (Harris & Mirande, 2013). Through telemetry and banding data, it has become clear that the birds using the Eastern migratory route (in the following referred to as the Eastern Black-necked Cranes) breed in northern Sichuan and southern Gansu provinces and mainly winter in northeast Yunnan and southwest Guizhou (Li & Li, 2005; Qian et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Direct human disturbances also play a non-negligible role in the decline of populations in the wild (Harris and Mirande 2013). For example, Zhou et al (2014b) found that approximately 2.1% of the RC population in the wild is lost each year due to poisoning, poaching, becoming entangled in fish nets and flying into power lines.…”
Section: Discussionmentioning
confidence: 99%
“…Their wintering area includes lower elevations on the Qinghai–Tibetan and Yunnan–Guizhou plateaus, as well as in Bhutan and occasionally in Nepal, Myanmar, Vietnam, and Kashmir (Li, 2014; Chandan et al, 2014). This species is facing threats from habitat loss and degradation induced by anthropogenic activities and climate change, with human disturbances particularly serious in their wintering grounds (Harris & Mirande, 2013; Li, 2014). Despite this, population increases over the past thirty years are believed to have occurred due to the benefits of grain waste in farmlands during winter (Harris & Mirande, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This species is facing threats from habitat loss and degradation induced by anthropogenic activities and climate change, with human disturbances particularly serious in their wintering grounds (Harris & Mirande, 2013; Li, 2014). Despite this, population increases over the past thirty years are believed to have occurred due to the benefits of grain waste in farmlands during winter (Harris & Mirande, 2013). However, conflicting results on black-necked crane habitat use have been reported from different wintering sites on the Yunnan–Guizhou Plateau.…”
Section: Introductionmentioning
confidence: 99%